KAJIAN KONFLIK PENGELOLAAN SUMBER DAYA HUTAN ANTARA PT. BINTANG LIMA MAKMUR DAN MASYARAKAT NEGERI SEPA KECAMATAN AMAHAI KABUPATEN MALUKU TENGAH - Hatalia, Siti Janaram; Silaya, Thomas M.; Imlabla, Wilma N. (PT. BARRINGTONIA ASIATICA LESTARI, 2026)
Forests have important ecological, economic, and socio-cultural roles for communities; however, their management often triggers conflicts between local communities and companies. This study aims to analyze the factors causing conflict and its characteristics between the Sepa Village community and PT. Bintang Lima Makmur in forest management. The research employed a descriptive qualitative method with purposive sampling involving 30 respondents consisting of community members and company employees. Data were collected through observation, questionnaires, interviews, literature study, and documentation, and analyzed using the Miles and Huberman model. The results show that the conflict is driven by three main factors: economic aspects (50% of respondents indicated high wage-related conflicts due to wage discrepancies, delays, and lack of transparency), environmental aspects (90% of respondents perceived moderate to high environmental impacts, including deforestation, pollution, and habitat degradation), and socio-cultural aspects (70% of respondents reported high conflict related to customary forests and land rights due to disruption of living space and sacred values). The conflict is destructive in nature as it causes losses and tensions, but it also has constructive potential in encouraging solutions and positive changes.